Dead evil? Constructing the 'Terrorist' in media obituaries. Issue 2 (4th May 2019) - Jarvis, Lee
ABSTRACT: Terrorists – or, better, those portrayed as 'terrorist' – are remembered in a multiplicity of ways after their death. In murals and music, in slogans and speeches, on t-shirts and online, in fiction and in film. This article focuses on one specific site of social memory – the newspaper obituary – to explore how these: narrate deceased 'terrorists' via reflection on their character, actions and significance; situate the deceased within relevant structural backgrounds; and, explain 'terrorist' behaviour via life-defining, formative experiences. It argues that these obituaries produce the (dead) 'terrorist' as a nuanced, complex and situated figure, one: whose designation as 'terrorist' is capable of contestation; who often possesses redeeming features; and, whose violences are situated within, and made possible by, wider structural contexts. In so doing, the article offers three contributions to knowledge: empirical, via the first sustained analysis of 'terrorist' obituaries as a distinctive mnemonic project; analytical, by elaboration on the processes through which past – rather than current/future – threats are made meaningful; and, conceptual, through reflection on the explanatory work that obituaries do in depicting 'terrorism's' causes.